English English - Laila Badriyatul Habibah; Rabiatul Adawiyah; Muhammad Arjuna Salim (Program Studi Pendidikan Biologi - Universitas Nias, 2026)
Education serves as a medium for acquiring knowledge, and along with the development of the modern era, learning has shifted from merely emphasizing content comprehension toward developing skills required to face real-world challenges. The integration of technology in education enables learning to be accessed anytime and anywhere. Classroom learning activities are conducted to achieve learning objectives; therefore, teachers may implement various innovative learning models such as Project-Based Learning (PjBL). PjBL encourages students to solve real-life problems through product development and has been proven effective in improving science problem-solving skills, particularly in biology learning related to health issues such as coronary heart disease. This study aims to develop a Google Sites–based learning media to provide information regarding the prevention of coronary heart disease. This study employed the 4D development model based on Sivasailam Thiagarajan (1974), this model consists of 4 stages: 1) define, 2) design, 3) develop, and 4) disseminate. The result of this study is an educational media entitled “Sehat Jantungku,” developed using Google Sites as a campaign media for the prevention of Coronary Heart Disease (CHD). This media was disseminated online and promoted through Instagram and TikTok to reach a broader and more targeted audience.